SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN JURUSAN MENGGUNAKAN FUZZY MULTIPLE ATRIBUTE DECISION MAKING DENGAN METODE SIMPLE ADDITIVE WEIGHTING STUDI KASUS PADA SMA ISLAM SULTAN AGUNG 1 SEMARANG - Dian Novita Handayani; Fitro Nur Hakim; Achmad Solechan (Jurusan Teknologi Informasi Universitas Semarang, 2014)
Problems that occur between major discrepancy with talent and competence are often experienced by high school students, therefore the role of decision support system for the selection of major is needed, so that teachers and students can assist in providing the appropriate department. The data collection process begins with the system requirements, system design, system creation process and the testing process. System design starts from designing the Unified Modeling Language (UML), Entity Relationship Diagram (ERD) and the design of the table. The process of ranking the major alternative use traditional methods of Simple Additive Weighting (SAW), which consists of a criteria subjects value, the value of attendance, the value of talent, values of Psikotest and quota of class. The final result in the form of majors recommendation from the calculation of the most high-ranking criteria. Recommended majors are expected to be the right advice for decision makers to make decisions majors, where the results showed that with this system have recommended majors conformity with the competence and talents of students by 74%.